Significance of factors influencing online knowledge sharing: A study of higher education in Pakistan - Noor Ul Ain Baig; Ajmal Waheed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Considering the importance of knowledge sharing in personal and professional life, this study focuses on behavior of knowledge sharing in online world. Henceforth, it explores the effect of different individual aspects like personality traits, engagement in online social networking sites and online community of practices on the online knowledge sharing behavior. In order to attain the goal of measuring the relationships, this study attempted a simultaneous multiple regression analysis technique to check their effect on online knowledge sharing behavior. One of the important and major contributions of this study is that the engagement of individuals in online social networking sites and online community of practices plays a very vital role in their online knowledge sharing behaviors in Pakistan. These findings are significant since they provide a better insight to the behavior of students when it comes to online knowledge sharing as a result of online social interaction. This study can find many utilities regarding the course contents and online study plans in educational institutes and personnel screening of human resource in commercial organizations.
Keywords: 330; online knowledge sharing; online community of practices; online social networking sites